The Meaning of Living in the Time of COVID-19. A Large Sample Narrative Inquiry - Venuleo, Claudia; Marinaci, Tiziana; Gennaro, Alessandro; Palmieri, Arianna (Frontiers in Psychology, 2020)
The spread of the COVID-19 pandemic has been a sudden, disruptive event which has strained international and local response capacity and distressed local populations. Different studies have focused on potential psychological distress resulting from the rupture of consolidated habits and routines related to the lockdown measures. Nevertheless, the subjective experience of individuals and the variations in the way of interpreting the lockdown measures remains substantially unexplored. Within the frame of Semiotic Cultural Psycho-social Theory (SCPT), the study pursued two main goals: first, to explore the Symbolic Universes (SU) through which Italian people represented the pandemic crisis and its meaning in their life; second, to examine how the interpretation of the crisis varies over societal segments with different socio-demographic characteristics and specific life challenges. An online survey was available during the Italian lockdown. Respondents were asked to write a passage about the meaning of living in the time of COVID-19. A total number of 1393 questionnaires (M = 35.47; DS =14.92; women: 64.8%; North Italy: 33%; Centre Italy: 27%; South Italy: 40%) were collected. The Automated Method for Content Analysis (ACASM) procedure was applied to the collected texts to detect the factorial dimensions underpinning (dis)similarities in the respondents’ discourses. Such factors were interpreted as the markers of latent dimensions of meanings defining the SU active in the sample. A set of chi square analysis allowed to explore the association between SU and respondents’ characteristics. Four SU were identified, labelled “Reconsider social priorities”, “Reconsider personal priorities”, “Live with emergency” and “Surviving a war”, characterised by the pertinentisation of two extremely basic issues: what the pandemic consists of (health emergency versus turning point) and its extent and impact (daily life versus world scenario). Significant associations were found between SU and all the respondents’ characteristics considered (sex, age, job status, job situation during lockdown and place of living). The findings will be discussed in the light of the role of the media and institutional scenario and psychosocial conditions in mediating the representation of the pandemic and in favoring or constraining the availability of symbolic resources underpinning people’s capability to address the crisis.